Drained Lake Basin classification based on Landsat-8 imagery, North Slope, Alaska 2014 -2019 - Bergstedt, Helena; Jones, Benjamin; Hinkel, Kenneth; Farquharson, Louise; Gaglioti, Benjamin; Parsekian, Andrew; Kanevskiy, Mikhail; Ohara, Noriaki; Rangel, Rodrigo; Grosse, Guido; Nitze, Ingmar (NSF Arctic Data Center, 2021)
This data set contains a classification of the North Slope, Alaska for drained lake basins (DLBs) based on Landsat-8 imagery of the years 2014-2019 and Arctic Digital Elevation Model (ArcticDEM) data. Drained lake basins (DLBs) are often the most common landforms in lowland permafrost regions in the Arctic (50% to 75% of the landscape). However, detailed assessments of DLB distribution and abundance are limited. This data set is based on a novel and scalable remote sensing-based approach to identify DLBs in lowland permafrost regions, using the North Slope of Alaska as a case study. The data set was validated against several prior sub-regional scale datasets and manually classified points. The study area covers greater than 71,000 square kilometers (km2), including a greater than 39,000 km2 area not previously covered in existing DLB data sets. Within the data set, three classes are present: DLB/ambiguous/noDLB. Areas classified as ambiguous could not be classified as DLB or noDLB with sufficient certainty. Users may decide on a case by case basis if they wish to use the conservative estimate of DLB area, therefore omitting areas classified as ambiguous, or to use all three classes.